2013
DOI: 10.1007/s11010-013-1595-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-protective effect of lipoic acid on injury induced by H2O2 in IPEC-J2 cells

Abstract: Alpha-lipoic acid (LA) is considered to be a universal antioxidant. The intestine is very sensitive to a wide range of stressors for it exposed in a complex microenvironment that usually contained excess free radicals. The objective of this study was to evaluate the pre-protective effect of LA on intestinal epithelial cell injury induced by H2O2. In this research, IPEC-J2 cells were divided into three groups: the control group, the H2O2-treated group, and the LA pre-protective group. Cell viability, intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
2
34
2
Order By: Relevance
“…Cai et al, reported that 10 µg/mL LA significantly increased the cytoactivity (MTT assay) of H 2 O 2 -stressed IPEC-J2 cells [31]. This differs from our findings where we observed no effect on cell viability of LA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cai et al, reported that 10 µg/mL LA significantly increased the cytoactivity (MTT assay) of H 2 O 2 -stressed IPEC-J2 cells [31]. This differs from our findings where we observed no effect on cell viability of LA.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, GA and LA pre-treatments were unable to significantly decrease the intracellular oxidative stress in IPEC-J2 cells. Previous research showed that LA pre-treatment had the tendency to decrease iROS in IPEC-J2 cells; however, this was not significant [31]. This study showed that GA increased the viability of H 2 O 2 stressed cells but was unable to significantly decrease iROS.…”
Section: Discussioncontrasting
confidence: 58%
“…Fe 2+ binding may attenuate oxidative stress and inhibit Fe 2+ -induced lipid peroxidation from iron overload. On the other hand, H 2 O 2 can significantly increase the intracellular free radicals, leading to serious DNA damage and significantly reduce superoxide dismutase, glutathione peroxidase, catalase, and lipase activity [27]. So ferrous iron chelatorclioquinol-may prevent its happening and reduce brain edema, but it would not happen with ferric iron chelatordeferiprone.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of inflammatory bowel disease is closely related to the oxidative stress generated by intestinal epithelia. The incidence of oxidative stress can cause intestinal epithelial cell damage; ROS can induce the activation of a variety of signaling pathways to promote intestinal epithelial cell apoptosis, including the PI3K pathway, which plays an important role in this process (84,85). The Jak/STAT3 and PI3K/Akt pathways are closely associated with the IL-6 receptor family; thus, it can be hypothesized that apelin/oxidative stress promotes the occurrence and development of intestinal inflammation, and may be related to the IL-6 receptor family.…”
Section: Apelin Regulates Oxidative Stress In the Occurrence Of Othermentioning
confidence: 99%